LAW ENFORCEMENT IN ONLINE FRAUD CASES IN THE JURISDICTION OF THE PEKANBARU CITY RESORT POLICE - Muhammad Isnaini; Yeni Triana; Indra Afrita (JILPR Journal Indonesia Law and Policy Review, 2026)
In reality, online fraud cases are increasingly prevalent within the Pekanbaru City Police Department, necessitating strict law enforcement. The purpose of this study is to analyze law enforcement in online fraud cases within the Pekanbaru City Police Department and to analyze the actions of the police in resolving online fraud cases within the Pekanbaru City Police Department. The method used is sociological legal research. Based on the research results, it is known that law enforcement against online fraud within the Pekanbaru City Police Department has shown progress, but still faces several obstacles. Legally, this crime is regulated in the Criminal Code and Law Number 19 of 2016 on Electronic Information and Transactions, which provides the legal basis for law enforcement officers to prosecute online fraud perpetrators. The Pekanbaru Police have investigated investigations and inquiries using digital technology, including tracking electronic transactions and identifying the perpetrators' social media accounts. Furthermore, law enforcement also prioritizes victim protection through legal assistance and mediation. However, several significant obstacles remain, including: the difficulty of tracing the perpetrators' identities due to the use of anonymous accounts or domiciles outside the jurisdiction, limited apparatus resources in dealing with technological developments, and slow coordination across relevant agencies such as banks and digital platforms. These obstacles can result in delayed legal proceedings, while victims' losses continue to mount. The Pekanbaru Police's actions in handling online fraud cases include prevention, investigation, prosecution, and law enforcement. In prevention, the Police conduct outreach through social media and educational campaigns to raise public awareness of fraudulent methods. During the investigation and inquiry phase, authorities utilize digital forensics, social media account monitoring, electronic transaction analysis, and coordination with relevant agencies. The City Police also detain eligible perpetrators, confiscate digital and physical evidence, and complete case files for trial.